Keberkesanan Proses Pengawasan Kelulusan Pelan Tambah Rumah di MPKK (Kajian Kes ke atas Taman Kenari, Kulim) - Rahmad (2012)
Housing is a basic of requirements for human life, every person who already has a house often think how to make their homes more beautiful, clean and comfortable. There are some of the home owners, especially those staying in low cost, a lot of build room additions, to get the space more comfortable and relaxed. This study focuses on the control plan approval process in building a home addition or amendment. Scope of this study is concentrated to homeowners who live in Kenari Park Kulim Housing and unlimited number Informants. Data were collected through interview and secondary data obtained from Kedah Kulim Municipal Council (MPKK). This research using a SWOT, (Strength, Weaknesses, Opportunities, threats) analysis, where the study was able to conclude, that there are still many homeowners community, yet to identify the building plan approval process renovation home, with 24-hour system. Some homeowners do not make additional plans home, because counting process requires a lot of the plan approval. So there should be an effective notification and monitoring, so that the image MPKK awake, and relationship with the people living in housing estates, will always be good and comfortable.